2021
DOI: 10.3390/en14206602
|View full text |Cite
|
Sign up to set email alerts
|

Biocrude Production from Hydrothermal Liquefaction of Chlorella: Thermodynamic Modelling and Reactor Design

Abstract: Hydrothermal liquefaction can directly and efficiently convert wet biomass into biocrude with a high heating value. We developed a continuous hydrothermal liquefaction model via Aspen Plus to explore the effects of moisture content of Chlorella, reaction pressure and temperature on thermodynamic equilibrium yields, and energy recoveries of biocrude. We also compared the simulated biocrude yield and energy recoveries with experiment values in literature. Furthermore, vertical and horizontal transportation chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Joshi et al [16] developed a 3D CFD model to simulate the influence of process parameters on suspension flow and solid particle transport, determined by the Prandtl number. However, previous studies mainly focused on predicting the HTL conversion efficiency of microalgae suspension in continuous tubular reactor mode [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Joshi et al [16] developed a 3D CFD model to simulate the influence of process parameters on suspension flow and solid particle transport, determined by the Prandtl number. However, previous studies mainly focused on predicting the HTL conversion efficiency of microalgae suspension in continuous tubular reactor mode [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Joshi et al developed a 3D CFD model to simulate the influence of process parameters on suspension flow and solid particle transport determined by the Prandtl number. However, previous studies mainly focused on predicting the HTL conversion efficiency of microalgae suspension in continuous tubular reactor mode [17]. Recently, few studies have been reported on the HTL process in continuous reactors on a pilot scale.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic model of hydrothermal reactions can assist studying the synthesis process, and has been widely adopted in the geology and the chemical industries [30][31][32][33][34][35][36]. Ma et al [37] studied the thermodynamics of hydrothermal synthesis of xonotlite from potassium silicate and Ca(OH) 2 , and provided theoretical guidance to the experimental process.…”
Section: Introductionmentioning
confidence: 99%